Silent Free Fall at Disease Onset: A Perspective on Therapeutics for Progressive Multiple Sclerosis - LoPresti, Patrizia (Frontiers in Neurology, 2018)
Central nervous system (CNS) degeneration occurs during multiple sclerosis (MS) following several years of reversible autoimmune demyelination and motor impairment. Progressive CNS degeneration appears later during the course of the disease, although it starts insidiously at the disease onset. Many different cell types are involved in the pathogenesis of MS. Furthermore, the response to the initial damage, which is specific for each individual, results in distinct pathogenetic pathways, and each MS patient presents unique therapeutic challenges. To effectively treat each MS patient, an identification of the various components of the disease should be done for each patient at the time of treatment. Until such individualized treatments become available, combined therapies directed at anti-inflammation, regeneration, and neuroprotection are the most effective treatments for this disease. This article focuses on targets and issues to be addressed at the disease onset for an effective treatment of progressive MS.